1999
DOI: 10.1212/wnl.53.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase upregulation in chronic inflammatory demyelinating polyneuropathy and nonsystemic vasculitic neuropathy

Abstract: The upregulation of MMP-2 and MMP-9 is a specific feature of CIDP and NSVN, and selective inhibitors of these enzymes could be used to prevent inflammatory tissue damage. The similar increase of MMP-2 and MMP-9 in both demyelinating (CIDP) and nondemyelinating (NSVN) neuropathies raises doubts about whether MMPs play a primary role in demyelination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 39 publications
3
54
0
2
Order By: Relevance
“…TAPI inhibits TNF-α activation by chelating TNF-α converting enzyme (TACE) and, at higher doses, MMP-9 and other MMPs. MMP inhibition also improves electrophysiologic nerve conduction and motor performance (Leppert et al, 1999;Hsu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TAPI inhibits TNF-α activation by chelating TNF-α converting enzyme (TACE) and, at higher doses, MMP-9 and other MMPs. MMP inhibition also improves electrophysiologic nerve conduction and motor performance (Leppert et al, 1999;Hsu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In the nervous system, MMPs produce neuroinflammation by controlling neurovascular permeability, immune cell recruitment, demyelination, cell necrosis, and apoptosis (Yong et al, 1998;Kieseier et al, 1999b, Rosenberg, 2002Lee et al, 2004a, Yong, 2005. MMP-9 is upregulated in experimental peripheral neuropathy models (La Fleur et al, 1996;Kherif et al, 1998;Ferguson and Muir, 2000;Siebert et al, 2001;Hughes et al, 2002;Platt et al, 2003;Demestre et al, 2004) and in patients with symptomatic neuropathy (Leppert et al, 1999;Mawrin et al, 2003;Renaud et al, 2003;Gurer et al, 2004). We have recently shown that MMP-9 gene deletion or pharmacologic inhibition reduces injury-induced macrophage recruitment and protects nerves from axonal degeneration .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, macrophages in the TrJ nerve maintain a close spatial relationship with myelinated nerve axons. Though it is known that macrophages contribute to peripheral nerve demyelination in both P0 and connexin-32 peripheral neuropathies (Schmid et al 2000;Carenini et al 2001;Kobsar et al 2002), and likely do so in the TrJ neuropathy, it is not fully clear if MMPs directly participate in myelin degradation (Leppert et al 1999). Nonetheless, both MMP-2 and MMP-9 may degrade myelin basic protein, a prominent constituent of peripheral nerve myelin (Chandler et al 1995), and an undetermined MMP activity degrades P0 (Cammer et al 1981).…”
Section: Discussionmentioning
confidence: 99%
“…In another animal model, experimental allergic neuritis, which is a model for the Guillain-Barré syndrome, there was expression of MMPs. Treatment with an inhibitor of MMPs improved electrophysiologic nerve conduction and motor performance (Redford et al, 1997;Hughes et al, 1998;Leppert et al, 1999).…”
Section: Mmps In Neuroinflammation In the Absence Of Hypoxiamentioning
confidence: 99%